Lower limb biomechanical differences between forehand and backhand forward lunges in amateur female badminton players - Xie, Zhonghao; Pan, Jing; Wu, Xingyu; Liang, Huiting; Chen, Bosi; Tan, Dongping; Wu, Meng; Huang, Zhiguan (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundForehand and backhand forward lunges are frequently performed in badminton, placing significant demands on the lower limbs. The purpose of this study was to examine the differences in lower limb biomechanics between these two lunge types in female amateur players.MethodsThis study involved 17 female amateur badminton players performing forehand and backhand forward lunges. Lower limb kinematics and dynamics were recorded using an eight-camera Vicon motion capture system and two AMTI force plates. Variables such as joint angle, range of motion, stiffness, and ground reaction forces measured during the stance phase were analyzed using paired t-tests. To account for the one-dimensional nature of joint angles, moments, and ground reaction forces, the analysis was performed using paired sample t-tests in Statistical Parametric Mapping 1D.ResultsThe forehand lunge exhibited a smaller hip flexion angle, greater hip internal rotation angle, and increased hip stiffness compared to the backhand lunge. The backhand lunge, in contrast, demonstrated a higher ankle varus angle and greater transverse plane hip range of motion. SPM1D analysis revealed significant differences in both the early (0%–10%) and late (80%–100%) phases of the stance phase. In the early phase, the backhand lunge showed a larger internal rotation moment at the hip, an external rotation moment at the knee, and a smaller knee extension moment. In the late phase, the forehand lunge revealed greater internal rotation moments at the hip, external rotation moments at the knee, ankle valgus moments, and smaller knee flexion moments.ConclusionThe backhand lunge requires greater hip internal rotation than the forehand lunge. Additionally, it is associated with higher ankle varus angles, which may increase the risk of ankle injuries. In contrast, the forehand lunge demonstrates greater hip stiffness, potentially reflecting an adaptation of the lower limb to varying directional demands. These findings emphasize the importance of incorporating targeted ankle and hip training exercises into conditioning programs.